Aplicación de técnicas de danza contemporánea José Limón y Martha Graham en un joven de 17 años con discapacidad parálisis cerebral en el periodo 2024 - Renata Alejandra, Bonilla Sarabia (2025)
In the present study, titled "Application of José Limón and Martha Graham Contemporary Dance Techniques in a 17-Year-Old Youth with Cerebral Palsy in the 2024 Period," an adapted program was implemented, applying contemporary dance techniques from José Limón and Martha Graham to a 17-year-old with cerebral palsy. This approach focused on adapting the principles of these techniques—such as weight, breathing, and body expression—to enhance the young person's mobility and self-expression. (Add methodology) Specific exercises were developed to allow the participant to explore their body safely, promoting physical and emotional development and fostering a deeper connection with their surroundings through movement. The program's expected outcomes included improvements in the youth's coordination, balance, and confidence, as well as an increase in their motivation and enjoyment of dance. Including individuals with disabilities in artistic activities not only enriches the individual's experience but also raises community awareness about diversity and the importance of providing equal opportunities. This program demonstrates that, through dance, it is possible to promote social integration and self-acceptance, paving the way toward a more inclusive society that recognizes the abilities of all its members.